Role of Endothelial Kinin B1 Receptor on the Membrane Potential of Transgenic Rat Aorta - Batista, C; Sales, V M; Merino, V F; Bader, M; Feres, T; Pesquero, J B (Physiological research, 2022)
The kinin receptors are classically involved in inflammation, pain and sepsis. The effects of the kinin B1 receptor agonist des-Arg9-bradykinin (DBK) and lipopolysaccharide (LPS) were investigated by comparing the membrane potential responses of aortic rings from transgenic rats overexpressing the kinin B1 receptor (B1R) in the endothelium (TGR(Tie2B1)) and Sprague Dawley (SD) rats. No difference in the resting membrane potential in the aorta's smooth muscle from the transgenic and SD rats was observed. The aorta rings from SD rats hyperpolarized only to LPS but not to DBK, whereas the aorta rings from TGR(Tie2B1) responded by the administration of both drugs. DBK and LPS responses were inhibited by the B1 receptor antagonist R715 and by iberiotoxin in both cases. Thapsigargin induced a hyperpolarization in the smooth muscle of SD rats that was not reversed by R715, but was reversed by iberiotoxin and this hyperpolarization was further augmented by DBK administration. These results show that the model of overexpression of vascular B1 receptors in the TGR(Tie2B1) rats represent a good model to study the role of functional B1 receptors in the absence of any pathological stimulus. The data also show that KCa channels are the final mediators of the hyperpolarizing responses to DBK and LPS. In addition, we suggest an interaction between the B1R and TLR4, since the hyperpolarization induced by LPS could be abolished in the presence of R715.
Keywords: bradykinin; membránové potenciály; Rats; In Vitro Techniques; potkani Sprague-Dawley; Bradykinin; Endothelium, Vascular; Aorta; Toll-Like Receptor 4; Lipopolysaccharides; aorta; receptor bradykininu B1; techniky in vitro; Membrane Potentials; krysa rodu Rattus; Rats, Transgenic; Receptor, Bradykinin B1; toll-like receptor 4; zvířata; thapsigargin; lipopolysacharidy; cévní endotel; Rats, Sprague-Dawley; potkani transgenní; Thapsigargin; Animals